Microservices with Spring Boot 3 and Spring Cloud Build resilient and scalable microservices using Spring Cloud, Istio, and Kubernetes - Larsson, Magnus; Larsson, Magnus (Packt Publishing, 2023)
Create and deploy production-grade microservices-based applications with this latest edition updated to Spring Boot 3, Java 17, and Spring Cloud 2022 Purchase of the print or Kindle book includes a free PDF eBookKey FeaturesBuild cloud-native production-ready microservices and stay ahead of the curveUnderstand the challenges of building large-scale microservice architecturesLearn how to get the best out of the latest updates, including Spring Boot 3, Spring Cloud, Kubernetes, and IstioBook DescriptionLooking to build and deploy microservices but not sure where to start? Check out Microservices with Spring Boot 3 and Spring Cloud, Third Edition. With a practical approach, you'll begin with simple microservices and progress to complex distributed applications. Learn essential functionality and deploy microservices using Kubernetes and Istio. This book covers Java 17, Spring Boot 3, and Spring Cloud 2022. Java EE packages are replaced with the latest Jakarta EE packages. Code examples are updated and deprecated APIs have been replaced, providing the most up to date information. Gain knowledge of Spring's AOT module, observability, distributed tracing, and Helm 3 for Kubernetes packaging. Start with Docker Compose to run microservices with databases and messaging services. Progress to deploying microservices on Kubernetes with Istio. Explore persistence, resilience, reactive microservices, and API documentation with OpenAPI. Learn service discovery with Netflix Eureka, edge servers with Spring Cloud Gateway, and monitoring with Prometheus, Grafana, and the EFK stack. By the end, you'll build scalable microservices using Spring Boot and Spring Cloud.What you will learnBuild reactive microservices using Spring BootDevelop resilient and scalable microservices using Spring CloudUse OAuth 2.1/OIDC and Spring Security to protect public APIsImplement Docker to bridge the gap between development, testing, and productionDeploy and manage microservices with KubernetesApply Istio for improved security, observability, and traffic managementWrite and run automated microservice tests with JUnit, test containers, Gradle, and bashUse Spring AOT and GraalVM to native compile the microservicesUse Micrometer Tracing for distributed tracingWho this book is forIf you're a Java or Spring Boot developer learning how to build microservice landscapes from scratch, then this book is for you. To get started, you need some prior experience in building apps with Java or Spring Boot.